2019
DOI: 10.1037/ocp0000121
|View full text |Cite
|
Sign up to set email alerts
|

“Some days won’t end ever”: Working faster and longer as a boundary condition for challenge versus hindrance effects of time pressure.

Abstract: Within the workplace, time constraints that create deadline pressure may jeopardize employees' goal attainment. In an attempt to overcome this stressful situation, employees may increase their efforts. We examine two strategies that are assumed to be stress reactions (coping) under conditions of high time pressure: working faster and working longer. We propose that these strategies moderate the relationship between time pressure and adverse health effects, as well as work engagement. In our daily diary study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
54
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 60 publications
3
54
2
Order By: Relevance
“…Although time urgency was more frequently categorized as a challenge demand, according to a meta-analysis (Mazzola & Disselhorst, 2019) and other empirical studies (e.g., Baethge et al, 2019;Gabriel et al, 2019;Kronenwett & Rigotti, 2019;Li et al, 2020), we expect a negative link between time urgency and work engagement. For instance, Baethge et al (2019) found that between-person level time pressure was negatively related to work engagement; Kronenwett & Rigotti (2019) also supported such a negative link. In summary, we propose that:…”
Section: Appraisal Of Job Demands As a Boundary Conditionmentioning
confidence: 65%
See 3 more Smart Citations
“…Although time urgency was more frequently categorized as a challenge demand, according to a meta-analysis (Mazzola & Disselhorst, 2019) and other empirical studies (e.g., Baethge et al, 2019;Gabriel et al, 2019;Kronenwett & Rigotti, 2019;Li et al, 2020), we expect a negative link between time urgency and work engagement. For instance, Baethge et al (2019) found that between-person level time pressure was negatively related to work engagement; Kronenwett & Rigotti (2019) also supported such a negative link. In summary, we propose that:…”
Section: Appraisal Of Job Demands As a Boundary Conditionmentioning
confidence: 65%
“…Further, role conflict and emotional demands are not consistently categorized as a challenge or a hindrance (e.g., Albrecht, 2015;Bakker & Sanz-Vergel, 2013;Crawford et al, 2010;Wincent & Örtqvist, 2011), whereas time urgency is generally seen as a challenge demand (Li et al, 2020). Although time urgency was more frequently categorized as a challenge demand, according to a meta-analysis (Mazzola & Disselhorst, 2019) and other empirical studies (e.g., Baethge et al, 2019;Gabriel et al, 2019;Kronenwett & Rigotti, 2019;Li et al, 2020), we expect a negative link between time urgency and work engagement. For instance, Baethge et al (2019) found that between-person level time pressure was negatively related to work engagement; Kronenwett & Rigotti (2019) also supported such a negative link.…”
Section: Appraisal Of Job Demands As a Boundary Conditionmentioning
confidence: 70%
See 2 more Smart Citations
“…Making matters even more blurry, developments from both research streams strongly suggest that time pressure (Baethge, Deci, Dettmers, & Rigotti, ) and creativity (Amabile et al, ) vary within individuals over time. Individuals may experience work days with more or less time pressure.…”
mentioning
confidence: 99%